Socio-economic Study of Slum to Estimate Vulnerability In Order To Develop Proper Resettlement/Rehabilitation Process. - Jayanandini G; Kamatchi Nivashini G. (International Journal of Urban Design and Development, 2023)
About 900 million people, by the lowest estimations, are currently residing in urban slums. This figure rises to 1.6 billion when informal settlements of various forms are included. This amounts to roughly a quarter of the world's urban population. A sizable portion of India's urban population resides in slums. They encounter substantial barriers when accessing adequate housing and basic amenities (water, sanitation, social facilities, etc.). Government agencies’ attempts to address these issues have fallen short because they have a limited understanding of the unique problems and priorities faced by those living in slums. This research makes recommendations for resettling slums in the city of Tirupur by first evaluating the vulnerability levels of slums using a vulnerability matrix and findings of socioeconomic surveys to evaluate the slum residents' standard of life. The requirements of slum communities must be understood in order to address them and develop a successful rehabilitation strategy. Because of the various degrees of precarity in India's slums, we need extremely detailed information about the city’s urban landscape. As part of the pilot research, four slums have been selected, and Survey carried out to collect data from 310 participants; participants have selected using a statistically simple random sampling method, and the results have been cross-tabulated to identify the most at-risk slums. Their needs are determined through focus groups, and the resulting cognitive thinking map will be utilized to guide rehabilitation efforts.
Keywords: Electricity; Public Transportation; Rehabilitation; socio-economic; vulnerability; water